2015
DOI: 10.1177/0040517515590412
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption analysis of thermally bonded high-loft nonwovens

Abstract: Sound absorption characteristics of specially designed high-loft nonwovens with minimum thickness were reported in this study. Three different polypropylene and polyester fiber-based high-loft, air-laid, and thermally bonded nonwovens varying in basis weight were produced. Heavier high-loft nonwoven samples at various thicknesses were formed using a specially designed mold. The sound absorption coefficients of samples with mass per unit areas ranging from 350 to 1575 g/m2 and with thicknesses ranging from 5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Thus, for high GSM fabrics (samples A, B and C) there are more fibers involved in the viscous losses and more acoustic energy is dissipated in the form of heat energy. 20,40 In the case of similar thickness (samples D, E, F and G), the increase of fabric GSM leads to an increase in airflow resistance. Since the flow resistance is less than the optimum, the sound absorption performance tends to increase as well.…”
Section: Sound Absorptionmentioning
confidence: 99%
“…Thus, for high GSM fabrics (samples A, B and C) there are more fibers involved in the viscous losses and more acoustic energy is dissipated in the form of heat energy. 20,40 In the case of similar thickness (samples D, E, F and G), the increase of fabric GSM leads to an increase in airflow resistance. Since the flow resistance is less than the optimum, the sound absorption performance tends to increase as well.…”
Section: Sound Absorptionmentioning
confidence: 99%
“…Thus, for high areal density samples there are more fibers involved in the viscous losses and more acoustic energy is dissipated in the form of heat energy. 20 In the case of similar thickness, the increase of fabric areal density leads to an increase in sound absorption performance. Based on this analysis, by comparing SAC of samples A, B, C, A1, B1, and C2, it is hard to conclude that samples produced by rotating perpendicular lapper have better sound absorption performance.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this phenomenon can be sample thickness and areal density differences. [19][20] Nonwoven thickness is a very important factor determining the sound absorption ability. Generally, the increase of thickness results in an increase of SAC at the low-frequency range.…”
Section: Sound Absorption Propertiesmentioning
confidence: 99%
“…High-loft nonwoven panel is known to have useful acoustic properties [ 14 ]. Although some studies related to the acoustic properties of this material can be found in the literature [ 14 , 15 ], there is a lack of research on recovered non-acoustic parameters via inverse method for this type of material. Moreover, there are only a few publications focusing on characterization of the homogeneity of nonwoven panels.…”
Section: Introductionmentioning
confidence: 99%